2006
DOI: 10.1007/s11055-006-0139-0
|View full text |Cite
|
Sign up to set email alerts
|

Objective measurement of human visual acuity by visual evoked potentials

Abstract: Electrophysiological studies were performed to measure the threshold (upper end of range) spatial frequency using visual evoked potentials and comparison with visual acuity neuron 26 healthy subjects. The aim of the present work was to create a method for objective measurement of visual acuity. This was addressed by initial measurements using a universally accepted method of visual stimulation and processing of electroencephalograms, which allows errors due to individual differences in visual system function t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 20 publications
0
8
0
Order By: Relevance
“…in contrast, most previous studies revealed that P1 latency has less inter-individual variation than P1 amplitude [42] , so particular emphasis was laid on the contribution of P1 latency to visual acuity, however, the major variability and the relative blunt modulation of P1 deduced by the traditional ways might limit its further application [21] . Kharauzov reported a strong logarithmic relationship between the threshold spatial frequency and visual acuity, allowing automated calculation of visual acuity from the electrophysiological data [43] . Besides the difference of the visual stimulus from our study, Kharauzov's study neglected the effect of visual angle.…”
Section: Discussionmentioning
confidence: 99%
“…in contrast, most previous studies revealed that P1 latency has less inter-individual variation than P1 amplitude [42] , so particular emphasis was laid on the contribution of P1 latency to visual acuity, however, the major variability and the relative blunt modulation of P1 deduced by the traditional ways might limit its further application [21] . Kharauzov reported a strong logarithmic relationship between the threshold spatial frequency and visual acuity, allowing automated calculation of visual acuity from the electrophysiological data [43] . Besides the difference of the visual stimulus from our study, Kharauzov's study neglected the effect of visual angle.…”
Section: Discussionmentioning
confidence: 99%
“…Steady-state VEP analysis in the frequency domain, sometimes following time domain averaging, typically uses only the first harmonic (at the stimulus frequency) for pattern on/offset stimuli or second harmonic (at the reversal rate) for pattern-reversal stimuli. Including one [26,[71][72][73][74][75][76][77] or even more [78,79] higher harmonics has been explored. Only one study combined harmonics for analysis, using a simple sum of the first and second harmonic magnitudes [76].…”
Section: Criteria For Vep Detectionmentioning
confidence: 99%
“…Including one [26,[71][72][73][74][75][76][77] or even more [78,79] higher harmonics has been explored. Only one study combined harmonics for analysis, using a simple sum of the first and second harmonic magnitudes [76]. In other steady-state VEP applications, the square root of summed harmonic powers has been used to combine harmonics for a ''global SNR'' [80].…”
Section: Criteria For Vep Detectionmentioning
confidence: 99%
“…To obtain better VEP results, preferably, most of the sweep spatial frequencies should be recognizable with a significant SNR to extrapolate the amplitude against spatial frequency. The sweep range of spatial frequency is about 3 to 30 cpd, corresponding to psychophysical optotypes from 1.0 to 0.0 logMAR in normal humans [ 7 , 36 , 77 , 83 , 85 , 87 , 97 , 98 ]. Besides, the sweep range was biased toward lower spatial frequencies in studies on infants and depended on their age, since their visual function develops over time [ 13 , 19 , 20 , 52 , 65 , 66 , 81 , 88 , 99 , 100 , 101 ].…”
Section: Effects Of Visual Stimulimentioning
confidence: 99%
“…The most widely used method was the linear extrapolation from the highest VEP amplitude response to the 0 µV amplitude baseline between VEP response amplitude and spatial frequency, and this spatial frequency of intersection with the x -axis (zero-response amplitude baseline) was determined as the VEP estimate of acuity. This linear extrapolation method was first proposed by Tyler et al [ 59 ] and subsequently used in many studies [ 13 , 14 , 17 , 19 , 20 , 36 , 62 , 63 , 65 , 66 , 73 , 74 , 75 , 79 , 80 , 81 , 82 , 85 , 86 , 88 , 90 , 91 , 92 , 93 , 94 , 95 , 96 , 98 , 99 , 100 , 101 , 102 , 103 , 106 , 108 , 110 , 121 , 122 , 123 , 124 , 125 , 126 , 127 , 128 , 129 , 130 ], and even in recent studies [ 52 , 77 , …”
Section: Effects Of Signal Acquisition and Analysismentioning
confidence: 99%